“Fronteira, identidade e bilinguismo”: uma sequência didática voltada para o ensino de português na zona de fronteira Brasil/Uruguai - (:unkn) unknown (Universidade Federal do Pampa, 2012)
This work aims to analyze the characterization of the Angolan national identity, through the expression of multiculturalism, represented in the literature, more specifically, in the book "Filhos da Pátria" (2008) written by John Melo. This book is an important example of literature as commitment to the social context.In the work are portrayed the different aspects of the Angolan society, as a result of ethnic diversity and also the colonial era, characterized by the imposition of European culture that influenced, directly, the national identity crisis in Angola. Filhos da Pátria (2008) shows for the readers with the "several Angolas" living in the same territorial area by means of a literature so rich, but still little publicized, even in Portuguese-speaking countries such as Brazil. The work aims also a short historical outline that specifies the reasons for Angola, and even Africa, are considered social mosaic. After all, the story influences the culture and identity of peoples, as well as they influence the story to find in literature an important source of representation. Besides the discussion that will be displayed in the first and second chapter, we elected three stories for the third chapter - “Ngola Kiluange”, “Shakespeare Ataca de Novo” and “Abel e Caim”- representing the theme about multiculturalism, the visible narratives strategies in the narrator’s intrusion and intertextuality.
Keywords: Letras; Fronteira; Bilinguismo; Ensino de português; Ensino; Frontera; Letras; Bilinguismo; Enseñanza de portugués; Letters; Border; Bilingualism; Portuguese teaching; CNPQ::LINGUISTICA, LETRAS E ARTES